2013
DOI: 10.1038/mp.2013.174
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy has a key role in the pathophysiology of schizophrenia

Abstract: Autophagy is a process preserving the balance between synthesis, degradation and recycling of cellular components and is therefore essential for neuronal survival and function. Several key proteins govern the autophagy pathway including beclin1 and microtubule associated protein 1 light chain 3 (LC3). Here, we show a brain-specific reduction in beclin1 expression in postmortem hippocampus of schizophrenia patients, not detected in peripheral lymphocytes. This is in contrast with activity-dependent neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
184
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 48 publications
(74 reference statements)
3
184
0
1
Order By: Relevance
“…Using biochemical and cell biology techniques, we showed multiple crucial interactions for ADNP, including the chromatin remodeling complex SWI/SNF , the RNA splicing machinery (Schirer et al 2014), protein translation (Malishkevich et al 2015), as well as the microtubule (Oz et al 2014) and autophagy systems (Merenlender-Wagner et al 2015). However, no good science can exist without listening and watching the society needs and hearing out the parents and wonderful caretakers of the ADNP children, which follows herein (Sandra Bedrosian Sermone, Our Undiagnosed Genetic Journey-ADNP mutation, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using biochemical and cell biology techniques, we showed multiple crucial interactions for ADNP, including the chromatin remodeling complex SWI/SNF , the RNA splicing machinery (Schirer et al 2014), protein translation (Malishkevich et al 2015), as well as the microtubule (Oz et al 2014) and autophagy systems (Merenlender-Wagner et al 2015). However, no good science can exist without listening and watching the society needs and hearing out the parents and wonderful caretakers of the ADNP children, which follows herein (Sandra Bedrosian Sermone, Our Undiagnosed Genetic Journey-ADNP mutation, 2015).…”
mentioning
confidence: 99%
“…Taking advantage of mouse genetics, we have shown that ADNP is crucial for brain formation (Pinhasov et al 2003) and learning and memory (Vulih-Shultzman et al 2007), in a sex-dependent manner (Malishkevich et al 2015;Kleiman et al 2015). Using biochemical and cell biology techniques, we showed multiple crucial interactions for ADNP, including the chromatin remodeling complex SWI/SNF , the RNA splicing machinery (Schirer et al 2014), protein translation (Malishkevich et al 2015), as well as the microtubule (Oz et al 2014) and autophagy systems (Merenlender-Wagner et al 2015).…”
mentioning
confidence: 99%
“…In this respect, it is interesting to add that ADNP regulates cathepsin expression [31]. ADNP was further associated with autophagy [32]. Developing an algorithm that will take into account variations and relationships among the potential biomarkers listed above and beyond will bring us closer to precision medicine.…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…It is a peptide snippet from the activity-dependent neuroprotective protein (ADNP), [1], a protein essential for brain formation [20,24] recently found to be mutated in autism [10], deregulated in schizophrenia [5,21] and in patients with Alzheimer's disease [29]. In this respect, multiple preclinical evaluations, as well as clinical trials with NAP (davunetide) showed efficacy of the peptide [18,19].…”
Section: Introductionmentioning
confidence: 99%